PROMOTING HEALTH AND CONFIDENCE: DEVELOPMENT AND EVALUATION OF A LOTERÍA GAME TO IMPROVE PERCEPTION AND ACCESS TO SERVICES IN THE HISPANIC/LATINO COMMUNITY OF JOHNSON COUNTY, KS. - Gibson, Michael (My University, 2025)
Johnson County Department of Health and Environment (JCDHE) serves a large and growing Hispanic/Latino community that often experiences language and access barriers. To meet this need, I developed and evaluated Health Lotería—a bilingual, culturally familiar game paired with a QR-coded digital resource index—to increase awareness of JCDHE services, strengthen trust, and make it easier for Spanish-preferring residents and their families to navigate and access care. I used Excel-based descriptive analysis of JCDHE’s Patagonia clinical data to contextualize need and guide implementation. Person-level fields reflect the most recent encounter, and service use was stratified by language preference. I complemented this with operational interpreter analytics (Propio) and community implementation observations collected during outreach. Evaluation included a brief, IRB-approved, bilingual survey using an implied-consent statement with no personal identifiers. Key findings reinforced the case for culturally and linguistically tailored outreach. Of 21,977 unique patients, 4,500 (20.48%) preferred Spanish; among them, 3,319 (73.76%) required an interpreter—evidence of a substantial communication barrier. In the same period, 7,309 patients (33.26%) self-identified as Hispanic/Latino, far exceeding the county’s 9.8% share, highlighting JCDHE’s critical role for this population. Propio data showed Spanish comprising roughly two-thirds of interpreter calls. Implementation through four community events demonstrated strong engagement and organic spread (e.g., residents requesting extra cards/business cards to share with parents and grandparents). The bilingual format, familiar imagery, and clear, plain-language resource links were consistently well-received. Continued survey analysis and website click-analytics will quantify changes in awareness, perceived cultural inclusivity, and ease of access to services. Overall, Health Lotería translated documented needs into an approachable tool that residents actually use. Early outcomes suggest the intervention is acceptable, culturally resonant, and operationally feasible. Finalized survey metrics and digital engagement data will support next-step refinement and scaling across high-demand programs (e.g., Maternal Health, Immunizations, Family Planning), where language supports are most critical.
Keywords: hispanic/latino communities; health equity; culturally tailored intervention; language access; community engagement; health Lotería (Lotería-based)